Over sea, under stone - Cooper, Susan, 1935- (New York: Simon Pulse, 1994)
Three siblings on vacation in Cornwall find an ancient manuscript which sends them on a dangerous quest that entraps them in the eternal battle between the forces of the Light and the Dark.
Keywords: Magic -- Fiction; Brothers and sisters -- Fiction; Fantasy; Cornwall (England : County) -- Fiction; England -- Fiction